Finite Speed of Propagation of Perturbations for the Cahn-Hilliard Equation with Degenerate Mobility (Journal of Partial Differential Equations, 2001)
This paper is devoted to the Cabn-Hilliard equation with degenerate mobility in two spatial variables with a typical case modelling thin viscous film spreading over a solid surface. We establish tbe existence of radial symmetric solutions with the property of finite speed of perturbations.
Keywords: Cahn-Hilliard equation; degenerate mobility; finite speed of propagation